Coffee Agroforestry as an Adaptive Mechanism for Forest Ecosystem Restoration: Integrating Conservation, Climate Mitigation, and Community Empowerment - Maulana, Bangkit; Susilowati, Lolita Endang; Suwardji, Suwardji; Mulyati, Mulyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Forest degradation and climate change represent some critical challenges threatening global ecosystem sustainability, particularly in tropical regions such as Indonesia. Agroforestry of coffee systems have been identified as an alternative approach capable of integrating biodiversity conservation, carbon sequestration, and improving farmer welfare. This study aims to comprehensively examine the contribution of coffee agroforestry to forest ecosystem restoration through a Systematic Literature Review analyzing of 22 scientific journal articles consisting of 12 Scopus-indexed international journals and 10 SINTA-accredited national journals from 2018-2025. Literature synthesis results indicate that coffee agroforestry systems can store average carbon stocks of 40-190 tons C/ha, enhance biodiversity by supporting regeneration of 90+ native tree species, and reduce erosion risk by 60-70%. Economically, coffee agroforestry contributes significantly to farmer income by 66.6% through product diversification and coffee quality improvement. The implementation of this system has also proven effective in climate change mitigation through microclimate regulation and atmospheric carbon absorption. This study recommends developing integrated policies supporting coffee agroforestry adoption as a sustainable ecosystems restoration strategy, with emphasis on technical assistance, economic incentives, and strengthening farmer institutions.